A viscous Cahn–Hilliard equation with periodic gradient dependent potentials and sources - Li, Yinghua; Cao, Yang (Mathematical Modelling and Analysis, 2012)
In this paper, we investigate the existence, uniqueness, attractivity and limiting process of solutions to the viscous Cahn–Hilliard equation with time periodic gradient dependent potentials and sources.